2020
DOI: 10.3390/vaccines8040580
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Hypothetical Zika Vaccine among Women from Colombia and Spain Exposed to ZIKV: A Qualitative Study

Abstract: Zika virus (ZIKV) can cause pregnancy loss and congenital Zika syndrome, among other poor health outcomes. The ZIKV epidemic in 2015–2017 disproportionately affected pregnant women in poor-resource settings. We aimed to understand perceptions and attitudes towards a hypothetical ZIKV vaccine, women’s willingness to be vaccinated, and potential barriers and facilitators for vaccine acceptance in 1) migrant women living in Spain who travelled to their countries of origin and were diagnosed with ZIKV infection du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Their answers referred to hypothetical participation, hence not being aware that enrolled participants actually counted on these sources at the time of recruitment. Nonetheless, their perspectives point to the right of pregnant women to decide about their participation in a trial after proper counseling from healthcare staff so that all possible risks and benefits of their participation are mentioned [18,19,22,23]. Therefore, there is a need to ensure an accurate communication channel in an empathetic atmosphere during the recruitment processes, especially in the delicate context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their answers referred to hypothetical participation, hence not being aware that enrolled participants actually counted on these sources at the time of recruitment. Nonetheless, their perspectives point to the right of pregnant women to decide about their participation in a trial after proper counseling from healthcare staff so that all possible risks and benefits of their participation are mentioned [18,19,22,23]. Therefore, there is a need to ensure an accurate communication channel in an empathetic atmosphere during the recruitment processes, especially in the delicate context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors influencing pregnant women's decisions to participate in a clinical trial might be a perceived personal benefit, quality of the information received, including communication on the risks and potential complications, the role of relatives in the decision-making process, the perceived voluntariness, uncertainties due to randomization as part of the research design, and unwillingness to take the study medication [19][20][21][22]. A qualitative study about the acceptability of a hypothetical ZIKV vaccine showed that women who had had a previous ZIKV infection during pregnancy hesitated to participate in a clinical trial; however, they would accept vaccination once the vaccine was commercialized [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, a major barrier for evaluation of ZIKV vaccines is the current context of reduced incidence after the ZIKV epidemic, which limits the plans for clinical development through phase II and III clinical trials [95,96]. Some issues would also need to be considered such the ethical implications of study design of vaccine trials in pregnant women living in areas with ZIKV transmission within an epidemic context [93], and strategies to effectively enrol pregnant women in ZIKV vaccine trials, as willingness to participate in previous hypothetical ZIKV vaccine trials has been reported to be low [97].…”
Section: Vaccines Against Zikvmentioning
confidence: 99%
“…Methodological limitations have also been found in the measures available for the evaluation of specific problems, such as attitudes towards papillomavirus (HPV) vaccines [ 22 ] or the scales developed to assess the confidence of parents towards childhood vaccination [ 23 ]. On the other hand, although it is true that attitudes towards vaccination vary according to the type of vaccine and the health problem [ 24 ], there are reasons to believe that a single measure can be an efficient way of identifying people with concerns related to vaccines in general [ 5 ]. A review of scales to study attitudes towards childhood vaccination reported that most shared indicators about beliefs about the benefits or importance of vaccination, confidence in vaccines and in health care providers, confidence in the legitimacy of authorities to require vaccination, vaccination harms, and perceived risks of infectious diseases [ 23 ].…”
Section: Introductionmentioning
confidence: 99%